2022
DOI: 10.3390/w14030418
|View full text |Cite
|
Sign up to set email alerts
|

Dynamization of Urban Runoff Pollution and Quantity

Abstract: At present, the annual loads from long-term series simulations are mostly used for the evaluation of rainwater management and treatment measures although the relevance of the temporal distribution of both pollution and quantity has a recognizable influence on the performance of the treatment. With the idea of dynamizing the simulation output values in relation to (i) single rainfall events, (ii) specific catchment characteristics, and (iii) the duration of the dry period between two rainfall events measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
3
2
0
Order By: Relevance
“…Table 7 and Figure 4G shows the substantially higher pollution of TSS at the Faisal site compared to that at El Dokki and Hadayek El-Ahram, where the traffic intensity at Faisal is more than twice that of El Dokki and Hadayek El-Ahram. These results are consistent with the previous literature [58,59]. Table 7 and Figure 5C,D,H show that the average concentration of dissolved Zn, Cu, Mg, and Fe was 3.91 mg/L, 1.82 mg/L, 46.25 mg/L, and 7.62 mg/L, respectively, at the Faisal-A1; whereas, it indicates 3.028 mg/L, 2 mg/L, 500 mg/L, and 7.21 mg/L, respectively, at El Dokki-B1.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Table 7 and Figure 4G shows the substantially higher pollution of TSS at the Faisal site compared to that at El Dokki and Hadayek El-Ahram, where the traffic intensity at Faisal is more than twice that of El Dokki and Hadayek El-Ahram. These results are consistent with the previous literature [58,59]. Table 7 and Figure 5C,D,H show that the average concentration of dissolved Zn, Cu, Mg, and Fe was 3.91 mg/L, 1.82 mg/L, 46.25 mg/L, and 7.62 mg/L, respectively, at the Faisal-A1; whereas, it indicates 3.028 mg/L, 2 mg/L, 500 mg/L, and 7.21 mg/L, respectively, at El Dokki-B1.…”
Section: Discussionsupporting
confidence: 94%
“…It is well-recognized that significant sources of metals in stormwater include tire wear and vehicle brake emissions [28]. The results showed that the levels of organic pollutants (COD and BOD) and disintegrated heavy metals (Zn, Cu, Pb, and Mn) were mainly due to the high traffic volume; these results are compatible with the previous literature [59]. The assessment of drinking water quality is a timely requirement amid emerging public health problems in this context, where the availability of safe water is at risk due to natural and man-made activities; the WQI was employed to analyze the variation in stormwater quality.…”
Section: Discussionsupporting
confidence: 89%
“…Figure 5 shows the basic statistics of EMC for TSS data for slice of runoff equal to 0.5-1 and 2 mm, while Figure 6 displays the basic statistics of the EMC for all the examined parameters (except for TSS, which is presented in Figure 5) with a slice of runoff equal to 1 mm. The graphs show that the EMCs obtained in earlier slices experience higher variability than the subsequent slices of runoff, which is consistent with the observation that several factors influence the initial pollution of wet-weather runoff in an urban catchment, including the peculiar features of the precipitation event, the duration of the previous drought period and the maintenance rules for urban surfaces [28,34].…”
Section: Resultssupporting
confidence: 86%
“…Water level and/or flow rate are commonly acquired with high frequency and adequate accuracy during monitoring campaigns in relation to sewerage. Conversely, despite considerable monitoring efforts, achieved water quality data are often limited or unreliable due to a lack of sample integrity, uncertainties and errors in the analytical process, with significant costs related to the monitoring equipment [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the first round of flooded irrigation (Figure S4), only 40-71 mg/L, 2.08-4.84 mg/L, and 2.42-3.14 mg/L of COD, TN, and TP were lost, respectively. The biggest difference between the two scenarios is the dramatic loss of particulate matter from rainfall, which is mechanistically the same as the first flush effect of agricultural non-point source pollution [46].…”
Section: Correlation Between Tn Tp Cod and Ses Lossmentioning
confidence: 99%